2020
DOI: 10.1002/admi.202000533
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Composition of Heterogeneous Lipid Bilayers to Stabilize Tethered Enzymes

Abstract: As surfaces for enzyme immobilization, lipid bilayers (LBs) have the potential to exhibit chaperone‐like activity, which can greatly enhance enzyme stability. Here, it is shown that this stabilizing effect can be generalized to a broad range of enzymes by modifying the mixed lipid composition based on the properties of the enzyme. This is demonstrated by analyzing the stability of nitroreductase, lipase, organophosphorus hydrolase, and lysozyme on LBs composed by mixing zwitterionic 1,2‐dioleoyl‐sn‐glycero‐3‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…This was done by constructing complementary cumulative squared displacement distributions (CCSDDs) for each state, under each experimental condition, and then fitting these distributions to a Gaussian mixture model containing three terms (See Materials and methods section for more details on distribution calculations, fitting, and calculation). represents the average instantaneous molecular diffusion coefficient at the shortest experimentally accessible time scale and is especially useful for systems where molecules change FRET states within a trajectory ( Chaparro Sosa et al, 2020 ; Chaparro Sosa et al, 2018 ; Langdon et al, 2015 ). Additionally, overall CCSDDs were constructed, in order to determine overall values of under each experimental condition.…”
Section: Resultsmentioning
confidence: 99%
“…This was done by constructing complementary cumulative squared displacement distributions (CCSDDs) for each state, under each experimental condition, and then fitting these distributions to a Gaussian mixture model containing three terms (See Materials and methods section for more details on distribution calculations, fitting, and calculation). represents the average instantaneous molecular diffusion coefficient at the shortest experimentally accessible time scale and is especially useful for systems where molecules change FRET states within a trajectory ( Chaparro Sosa et al, 2020 ; Chaparro Sosa et al, 2018 ; Langdon et al, 2015 ). Additionally, overall CCSDDs were constructed, in order to determine overall values of under each experimental condition.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that the stability and activity of enzymes tethered to mixed lipid bilayers was directly related to lipid composition. Furthermore, using single-molecule methods, we found that that the enhancement in enzyme stability and activity upon varying lipid composition was due to a chaperone-like effect of the bilayer, whereby the bilayer actively mediated the refolding of denatured enzyme molecules at the bilayer–solution interface. , We therefore hypothesize that tuning the composition of mixed DOPG/DOPC vesicles may have a similar effect on the stabilization of Aβ. Specifically, by acting as a molecular chaperone, the mixed DOPG/DOPC vesicles may degrade Aβ fibrils and, moreover, catalyze Aβ refolding.…”
mentioning
confidence: 87%
“…Here, we studied the interactions between Aβ peptides/fibrils and unilamellar vesicles composed of mixtures of zwitterionic and anionic phospholipids, specifically 1,2-dioleoyl- sn -glycero-3-phosphocholine (DOPC) and 1,2-dioleoyl- sn -glycero-3-phosphoglycerol (DOPG), respectively. This choice was motivated by our previous observations that mixed lipid bilayers had remarkable stabilizing effects on enzymes tethered to lipid bilayers, especially when the bilayer and protein exhibited like net electrical charges . While studying the interaction of mixed DOPG/DOPC vesicles with Aβ peptides/fibrils, we investigated the effect of vesicle composition on both the prevention of fibrillation in solution, as well as the disruption of preformed fibrillar aggregates.…”
mentioning
confidence: 99%
“…Recent findings from dynamic single-molecule (SM) experiments have significantly altered our view of how the functional utility of enzymes upon immobilization may be improved. Based on these findings, it has become apparent that both long-term stability and the immediate retention of enzyme activity and structure during immobilization to surfaces are critical. Importantly, because long-term stability and immediate retention of activity and structure involve different mechanisms, different strategies may be required to address each of these aspects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, while the long-term stability of immobilized enzymes may be enhanced by tethering enzymes to materials that stabilize the native state of the enzyme and/or promote refolding of denatured enzyme molecules, the immediate retention of activity and structure may be enhanced by controlling the exploration of the surface by the enzyme prior to reaction with the material. Although there has been extensive work on improving the long-term stability of immobilized enzymes, , preventing the immediate denaturation of enzymes has received far less attention.…”
Section: Introductionmentioning
confidence: 99%